Beyond spot advertising - Eaves, Mark (Henry Stewart Talks, 2009)
New forms of television led communications, The shape of things to come, TV audience fragmentation, TV sponsorship, Branded content, The interactive revolution, The transition to on demand, A new distribution universe, The passive and the active viewer